2010
DOI: 10.1258/jrsm.2010.100256
|View full text |Cite
|
Sign up to set email alerts
|

Visual art in hospitals: case studies and review of the evidence

Abstract: Summary In 2006 a Department of Health Working Group on Arts and Health reported that the arts have ‘a clear contribution to make and offer major opportunities in the delivery of better health, wellbeing and improved experience for patients, service users and staff alike’. In this review we examine the evidence underpinning this statement and evaluate the visual art of three of Scotland's newest hospitals: the Royal Infirmary of Edinburgh, the new Stobhill Hospital, and the new Victoria Infirmary in Glasgow. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 18 publications
(32 reference statements)
1
62
0
2
Order By: Relevance
“…Aside from the architecture of the hospital building itself, the introduction of visual art into hospitals (see Lankston et al 46 for an evaluation of its benefits) is one example of the way in which designers have attempted to make hospitals into therapeutic landscapes. These interior designs have particularly focused on integrating 'nature' 47 and 'home' 38 into the institutional space because they are two arenas strongly imbued with the qualities of a 'therapeutic landscape'.…”
Section: Development Of Birth Centresmentioning
confidence: 99%
“…Aside from the architecture of the hospital building itself, the introduction of visual art into hospitals (see Lankston et al 46 for an evaluation of its benefits) is one example of the way in which designers have attempted to make hospitals into therapeutic landscapes. These interior designs have particularly focused on integrating 'nature' 47 and 'home' 38 into the institutional space because they are two arenas strongly imbued with the qualities of a 'therapeutic landscape'.…”
Section: Development Of Birth Centresmentioning
confidence: 99%
“…A series of analyses and scientific research demonstrated effectively the positive outcomes resulting from the incorporation of artistic performances and activities into healthcare experience and visual art implementation in medical settings. The arts create a safe and supportive environment, improve the physical health and the well-being of patients, their relatives and medical staff [7][8][9]. Artistic interventions may include various dimensions of arts, however this article will focus on the most popular type: the visual art.…”
Section: Visual Art As Medication -Research Reviewmentioning
confidence: 99%
“…It is indicated that the colours that elicit high levels of pleasure with low levels of arousal are most likely to induce a state of calm, while those causing high levels of arousal may provoke anxiety [9]. Several studies on the impact of colour on different factors associated with well-being indicate a shared conclusion that colour impacts healthcare outcomes by reducing stress and enhancing the sense of well-being, improving patients' sleep and reducing length of stay, helping to overcome user's spatial disorientation and diminish medical errors.…”
Section: Visual Art As Medication -Research Reviewmentioning
confidence: 99%
“…Aside from the architecture of the hospital building itself, the introduction of visual art into hospitals (Lankston et al 2010) is one example of the way in which designers have attempted to mould hospitals into more therapeutic landscapes. These interior designs have particularly focused on integrating 'nature' (Conradson 2005) and 'home' (Gilmour 2006) into the institutional space because they are two arenas strongly imbued in the public imagination with the qualities of a 'therapeutic landscape' (Gesler 1992).…”
Section: The Literature On Place and Therapeutic Spacesmentioning
confidence: 99%